Comparative analysis of COVID-19 and influenza prevalence among Egyptian pilgrims returning from Hajj and Umrah in 2022: epidemiology, clinical characteristics, and genomic sequencing - Amr Kandeel; Manal Fahim; Ola Deghedy; Hala BahaaEldin; Wael H. Roshdy; Mohamed Kamal Khalifa; Ahmed Kandeil; Rabeh El Shesheny; Amel Naguib; Mohamad AbdelFatah; Salma Afifi; Khaled Abdel Ghaffar (BMC, 2024)
Abstract Purpose To describe the changes that occurred in the SARS-CoV-2 and influenza Prevalence, epidemiology, clinical picture, and prevalent genotypes among the Egyptian pilgrims returning from Hajj and Umrah 2022 seasons. Methods Pilgrims were contacted at the airport and invited to participate in the survey. Pilgrims who consented were interviewed using a standardized line list that included participant demographics, respiratory symptoms if any, previous COVID-19 infection, influenza vaccination whereas COVID-19 vaccination information were collected from vaccination cards. Participants were asked to provide throat and nasopharyngeal swabs for SARS-CoV-2 and influenza testing using RT-PCR and a subset of isolates were sequenced. Descriptive data analysis was performed to describe the epidemiology and clinical symptoms of SARS-CoV-2 and influenza. Prevalence rates of SARS-CoV-2 and influenza during Hajj were calculated and compared to Umrah surveys using chi2 and t-test with a significance level < 0.05. Results Overall, 3,862 Egyptian pilgrims enrolled, their mean age was 50.5 ± 47 years, half of them were > 50 years of age and 58.2% were males. Of them, 384 (9.9%) tested positive for SARS-CoV-2 and 51 (1.3%) for influenza viruses. Prevalence of SARS-CoV-2 infections (vaccine breakthrough) increased significantly between the Umrah and Hajj surveys (6.7% vs. 9.9%, p < 0.001), and variants of the virus varied considerably. Whereas no significant difference was found in influenza prevalence, vaccine coverage and vaccine breakthrough infection rates (11.7 vs. 9.2%, 26.9 vs. 26.8%, and 1.4 vs. 1.1% respectively). Conclusions SARS-CoV-2 prevalence among Egyptian pilgrims returning from Hajj in July increased with reduced vaccine effectiveness compared to Umrah in March 2022 suggesting a possible wave of SARS-CoV-2 in the upcoming winter.